Strain Adjustment Realizes the Photocatalytic Overall Water Splitting on Tetragonal Zircon BiVO4. Issue 15 (22nd March 2022) - Dai, Dujuan; Liang, Xizhuang; Zhang, Beibei; Wang, Yuanyuan; Wu, Qian; Bao, Xiaolei; Wang, Zeyan; Zheng, Zhaoke; Cheng, Hefeng; Dai, Ying; Huang, Baibiao; Wang, Peng
Abstract: Overall water splitting to generate H2 and O2 is vital in solving energy problem. It is still a great challenge to seek efficient visible light photocatalyst to realize overall water splitting. In this work, the tetragonal zircon BiVO4 is prepared by epitaxial growth on FTO substrate and its overall water splitting reaction is studied. Under the influence of epitaxial strain, the conduction band position shifts negatively and beyond H + /H2 reduction potential (0 V vs NHE), which enables it to possess the photocatalytic hydrogen evolution activity. After loading cocatalysts, the overall water splitting ( λ > 400 nm) is realized (H2 : ≈65.7 µmol g −1 h −1, O2 : ≈32.6 µmol g −1 h −1 ), and the value of solar hydrogen conversion efficiency is 0.012%. The single‐particle photoluminescence (PL) spectra and PL decay kinetics tests demonstrate the cocatalysts are beneficial to the separation and transfer of carriers. The new strategy of adjusting the band structure by strain is provided. Abstract : Under the influence of epitaxial strain, the conduction band position of tetragonal zircon BiVO4 grown on FTO substrate can across the H + /H2 reduction potential (0 V vs NHE), achieving overall water splitting under visible light. This work provides a new strategy of adjusting the band structure by strain for performing photocatalytic overall water splitting on BiVO4 .